PERCEIVED SERVICE QUALITY AND TRUST ON SATISFACTION: CUSTOMERS PERSPECTIVES IN THE BANKING SECTOR - Ratna Roostika (University of Merdeka Malang, 2011)
The purpose of this study was to examine the relationship between service quality, trust and satisfaction in thebanking sector. Specifically, the dimensions of service quality were modeled to have direct influence on bothsatisfaction and trust. An empirical analysis was carried out in which the service performance scale wasadapted to the study. 160 out of 200 questionnaires were valid for data analysis. The data was obtained byusing a structured questionnaire to bank customers. Structural equations model using Partial least Squares(PLS) was applied to analyze the proposed model. The findings partly confirmed the relationship betweenservice quality dimensions on trust since tangible dimension was not significant. However, all service qualitydimensions were significant in predicting satisfaction. Practically, the findings suggest that banks couldcreate satisfaction through service quality and trust. Therefore, all staffs should establish and maintain confidencein providing service quality and building trust for customers. Theoretically, besides adding trust in theservice quality and satisfaction relationship, the study was conducted in developing countries. This willenhance the generalization of service quality measures and validate the model in the wider area.